The gas bladder of Heterotis niloticus (Cuvier, 1829). (6th April 2023) - Icardo, José M.; Alesci, Alessio; Kuciel, Michal; Zuwala, Krystyna; Guerrera, Maria C.; Zaccone, Giacomo
Abstract: This work reports on the structural characteristics of the respiratory gas bladder of the osteoglossiform fish Heterotis niloticus . The bladder‐vertebrae relationships are also analyzed. A slit‐shaped orifice in the mediodorsal pharyngeal wall is surrounded by a muscle sphincter and serves as a glottis‐like opening to the gas bladder. The dorsolateral internal surface of the gas bladder is lined by a parenchyma of highly vascularized trabeculae and septa displaying an alveolar‐like structure. The trabeculae contain, in addition to vessels, numerous eosinophils probably involved in immune responses. The air spaces are endowed with a thin exchange barrier indicating a good potential for respiratory gas exchange. The ventral wall of the gas bladder is a well‐vascularized membrane that exhibits an exchange barrier in the luminal face and an inner structure dominated by the presence of a layer of richly innervated smooth muscle. This is suggestive of an autonomous adjustability of the gas bladder ventral wall. The trunk vertebrae show large transverse processes (parapophyses) and numerous surface openings that lead into intravertebral spaces that become invaded by the bladder parenchyma. Curiously, the caudal vertebrae show a regular teleost morphology with neural and hemal arches, but have similar surface openings and intravertebral pneumatic spaces. The African Arowana hence rivals the freshwater butterfly fish Pantodon in its exceptional role of displaying postcranial skeletal pneumaticity outside of Archosauria. The possible significance of these findings is discussed. Abstract : The respiratory bladder of Heterotis niloticus is an alveolated structure, highly vascularized, that accumulates eosinophils that may be involved in immune defense. The bladder dorsolateral and ventral walls exhibit exchange barriers indicating high capability for gas exchange. The trunk vertebrae show parapophyses and intravertebral pneumatic spaces that are invaded by the bladder tissue. Caudal vertebrae show the typical teleost configuration but, in the absence of respiratory tissue, show similar surface openings and vertebral pneumatization.